Criminal Fine In The Crime Of Alcoholic Drinks Smuggling - Indawan, Ana Aqila Haya Syaharani; Susanti, Emilia; Shafira, Maya (VIVA THEMIS, 2024)
The aim of this research is to determine the criminal sanctions imposed by fines on perpetrators of the crime of smuggling alcoholic beverages. The method used in this research is a normative legal research method using a statute problem approach. The results of this research are that the forms of sanctions given to perpetrators of the crime of smuggling alcoholic beverages are categorized based on the smuggling carried out in the import and/or export sector. Smuggling carried out in the import sector is subject to sanctions with a minimum imprisonment of 1 (one) year and a maximum imprisonment of 10 (ten) years and a fine of at least IDR 50,000,000.00 (fifty million rupiah) and a maximum of IDR 5,000. 000,000.00 (five billion rupiah), and smuggling in the export sector with a minimum prison sentence of 1 (one) year and a maximum prison sentence of 10 (ten) years and a fine of at least Rp. 50,000,000.00 (fifty million rupiah ) and a maximum of IDR 5,000,000,000.00 (five billion rupiah).